MANAJEMEN STRATEGI OTORITAS JASA KEUANGAN (OJK) KALIMANTAN BARAT DALAM EDUKASI LITERASI KEUANGAN - Munawir Munawir; Maskupah Maskupah; Reza Kurniawan (Cross-border, 2019)
ABSTRACT From this research, it is seen that the level of financial literacy, especially for Indonesia, is still quite low, namely 32% compared to the literacy level of other countries such as Malaysia, Sri Lanka and Africa, the level of financial literacy in Indonesia is still lower. "(Literacy rate) of other countries such as Malaysia 36%, Sri Lanka 35% and South Africa 42%,". So that it causes public mistakes in investing and the emergence of fraud cases in the regions even though there have been many activities carried out such as socialization or seminars but according to researchers these activities are still inefficient in educating financial literacy. This study aims to reveal: 1. To find out how the strategic management of the financial services authority. 2. To determine the level of financial literacy in West Kalimantan in 2016. 3. Impact of financial literacy in West Kalimantan. The method used in this research is descriptive method with a qualitative approach. Data collection techniques used are, interview techniques, documentation and direct observation. For the data analysis technique that the researchers did, they went through three processes of description, analysis and interpretation. While the technique of checking the validity of the data the researchers used were credibility (the quality of the research in generating trust), transferability (external validation), dependability (confirming the equality of the data when re-examining) confirmability (checking the research again). Conclusion: 1). Financial literacy education strategy carried out by OJK Kal-Bar: Phase 1. Mapping cases or research, stage 2. Determining the priority scale, and stage 3. Determining appropriate activities, Stage 4. Following processes and guidelines in accordance with the national strategy in financial literacy , stage 5. Evaluation 2). The level of financial literacy in West Kalimantan is 30.55%. 3). It can be seen from the level of financial literacy in West Kalimantan which shows the level of well literacy, which means that the people of West Kalimantan have knowledge, confidence and have skills in using financial service products.